2010
DOI: 10.1021/ef900537m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coal Ash Composition on Ash Fusion Temperatures

Abstract: The ash fusion temperatures (AFTs) of coal mineral matter at high temperature are important parameters for all gasifiers. Experiments have been conducted in which mixtures of selected coal ashes and SiO 2 , Al 2 O 3 , CaO, Fe 2 O 3 , and MgO were subjected to the standard test for ash fusibility. The computer software package FactSage has been used to calculate the liquidus temperatures of coal ash samples and the proportions of the various phases present as a function of temperature. The results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(93 citation statements)
references
References 27 publications
0
89
0
Order By: Relevance
“…Liquid temperature of the slag was determined for the mineral matter that it contained. 46 On the basis of the oxide composition of the slag, the proportion of liquid phase generated and the compositions of remaining liquid phase were evaluated at different temperatures. FactSage is a thermodynamic equilibrium model.…”
Section: Factsage Modelingmentioning
confidence: 99%
“…Liquid temperature of the slag was determined for the mineral matter that it contained. 46 On the basis of the oxide composition of the slag, the proportion of liquid phase generated and the compositions of remaining liquid phase were evaluated at different temperatures. FactSage is a thermodynamic equilibrium model.…”
Section: Factsage Modelingmentioning
confidence: 99%
“…Earlier studies have explored the influence of components on ash fusibility or viscosity [20][21][22], but not much data is available on sintering characteristics. It has been concluded that high SiO 2 /Al 2 O 3 ratios (S/As) and low concentrations of basic oxides account for the high ash fusion temperatures of most Australian bituminous coal ashes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Under oxidizing conditions, the ratio of SiO 2 and CaO is most strongly correlated with temperature. Song et al [60] investigated CaO, Fe 2 O 3 , and MgO on fusion temperatures under argon using the thermodynamic computer package FactSage. The fusion temperatures of coal ash decrease with increasing CaO, Fe 2 O 3 , and MgO contents then increase after reaching a minimum; for example, when CaO is higher than 35% the fusion temperature increases rapidly [50].…”
Section: Ash Fusibility and Ash Flow Temperaturementioning
confidence: 99%